Handheld Laser-Induced Breakdown Spectroscopy (hLIBS) Applied to On-Site Mine Waste Analysis/Evaluation in View of Its Recycling/Reuse - Giorgio S. Senesi (Chemosensors)
Nowadays, the recovery/recycling/reuse of mining and mineral processing wastes is considered the best approach to support the circular economy and sustainability of mining and metal extraction industries. Mine wastes can be used to restore surface and subsurface land damaged by mining operations, generate fuel for power plants, further extract their component minerals, and as building materials additives. The aim of this perspective paper is to briefly highlight and focus on the most recent analytical potential and performance achieved by handheld laser-induced breakdown spectroscopy (hLIBS) instrumentation in the perspective of its future application in the mine waste sector to quickly identify on-site the presence of useful chemical elements for their possible sustainable recovery.